Unani perspective of Khatmi (Althaea officinalis) - Fahamiya, N.; Shiffa, M.S.M.; Aslam, M.; Farzana, M.U.Z.N. (Journal of Pharmacognosy and Phytochemistry, 2016)
Khatmi (Althaea officinalis), commonly known as Marsh Mallow is one of the important medicinal plant used in Unani medicine. Khatmi is a perennial plant with light brown coloured, long and thick root, ovate-cordate, slightly toothed leaves and pale pink or pale purple coloured flowers. Root, leaves, flowers and seeds are mainly used in medicine. All the parts contain mucilage. It is having emmollient, analgesic, astringent, haemostatic, expectorant, luxative, cleansing, demulcent, concoctive, diuretic, emmenagogue, anti-inflammatory and exhilarant properties. In Unani medicine, Khatmi has been used for several centuries to treat inflammatory disorders like metritis, enteritis, mastitis, arthritis, colitis, bronchitis, gastritis, etc. It also has been used for other ailments like catarrh, renal calculai, pityriasis, tremor, dysuria, dysentery, haemoptysis, whooping cough and many more. Though, this plant is used for many varieties of disease, very few actions of this plant have been proven scientifically. Hence, this review will help to conduct scientific studies in unexploited potencial of this plant.
Keywords: Khatmi; Althaea officinalis; Marshmallow; mucilage; Unani